2018
DOI: 10.7759/cureus.3016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Inpatient Palliative Care Consultation in Terminally Ill Cancer Patients

Abstract: Limited data are available to guide the timing of palliative care involvement in the treatment of cancer. We describe the referral patterns of inpatient palliative care consultations(IPCC) in advanced cancer patients in a tertiary care center.Methods: A retrospective review was performed of IPCC for cancer patients from January 1, 2014, to December 31, 2014. Descriptive statistics are reported.Results: IPCCs were requested for 245 cancer inpatients, of which 130 were male (53.1%) and 115 (46.9%) were female; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Perceived time to death or death acting as a mediator on the relationship between race and receipt of IPCC may contribute to the mixed findings of the association between race and IPCC in the literature. [21][22][23][24][25][26] Although several studies have found higher odds of IPCC for hospitalized black patients with cancer, a few have found no difference or higher odds of IPCC for black patients compared to white patients. [21][22][23][24][25][26] However, only one of these studies investigated death as a mediator of receipt of IPCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived time to death or death acting as a mediator on the relationship between race and receipt of IPCC may contribute to the mixed findings of the association between race and IPCC in the literature. [21][22][23][24][25][26] Although several studies have found higher odds of IPCC for hospitalized black patients with cancer, a few have found no difference or higher odds of IPCC for black patients compared to white patients. [21][22][23][24][25][26] However, only one of these studies investigated death as a mediator of receipt of IPCC.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Although several studies have found higher odds of IPCC for hospitalized black patients with cancer, a few have found no difference or higher odds of IPCC for black patients compared to white patients. [21][22][23][24][25][26] However, only one of these studies investigated death as a mediator of receipt of IPCC. 25 The absence of measurement of the potential mediator of death could explain the differences among these studies as highlighted by our findings of a transposed relationship between black race and IPCC when stratified by death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Delay of initiation of outpatient palliative care consultation among non-Hispanic Black cancer patients also highlights a racial disparity. 53 Ahluwalia and colleagues (2018) examined 139 systematic reviews published after 2013, when the third edition of National Consensus Project Clinical Practice Guidelines for Quality Palliative Care was published. The main objective of this comprehensive review was to provide a synthesis of the evidence in palliative care to improve the next (fourth) edition of these guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…29 Given the severity of disease and poor prognosis in this patient cohort, we expected a higher consultation rate. [33][34][35][36][37][38] It is possible that providers did not consider involvement of palliative care until all life-prolonging measures had been attempted or exhausted. This is supported by the low rates of documented GoC discussions, leaving little time to involve palliative care providers prior to a patient's death.…”
Section: Discussionmentioning
confidence: 99%